Enhancing Village Officials Competence Through the Socialization of Appropriate Tecnology and Training on RAB and DED - Rifaldo Pido; Rahman Abdul Djau; Yohanes P. Erick; Ilyas Ichsan; Abdul Kadir Zailani Oli’i (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
Improving the capacity of village officials in development planning is very important to support the effectiveness of budget management and program implementation at the village level. This community service activity aims to improve the competence of village officials through the socialization of the application of appropriate technology and training in the Budget Plan (RAB) and Detail Engineering Design (DED). The monitoring results show that the level of participation of village officials in this activity is quite high, with a value of 90% of participants attending all training sessions, the initial evaluation through a pre-test showed that participants' understanding of the preparation of RAB and DED was still limited. However, after participating in the training, there was an increase in understanding of 75% based on the results of the Post-test. In addition, 80% of participants understand the basic stages of making simple RAB and DD as the final task of the training.